2022
DOI: 10.3389/fvets.2022.1027967
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the yak rumen eukaryotic community and metabolome characteristics in response to feed type

Abstract: With diversification of yak breeding, it is important to understand the effects of feed type on the rumen, especially microbiota and metabolites. Due to the unique characteristics of yak, research on rumen microbes and metabolites is limited. In this study, the effects of two diet types on rumen eukaryotic microflora and metabolites were evaluated using the Illumina MiSeq platform and liquid chromatography-mass spectrometry (LC-MS). All identified protozoa belonged to Trichostomatia. At the genus level, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Henderson et al, which assessed the protozoa community across different cohorts of different species of ruminants, similarly reported a strong host individuality in protozoa communities even within specific cohorts 8 . Furthermore, a recent study in the yak rumen found several differences in the relative abundance of some protozoa species in response to feed type, but overall community structure as measured by Beta diversity was not significantly different as opposed to bacterial or the fungal community 9 . Our results further support the notion of a higher stability of protozoa in the rumen, which was observed by examining the community changes when the animal diet was switched (Figure 1c).…”
Section: Discussionmentioning
confidence: 81%
“…Henderson et al, which assessed the protozoa community across different cohorts of different species of ruminants, similarly reported a strong host individuality in protozoa communities even within specific cohorts 8 . Furthermore, a recent study in the yak rumen found several differences in the relative abundance of some protozoa species in response to feed type, but overall community structure as measured by Beta diversity was not significantly different as opposed to bacterial or the fungal community 9 . Our results further support the notion of a higher stability of protozoa in the rumen, which was observed by examining the community changes when the animal diet was switched (Figure 1c).…”
Section: Discussionmentioning
confidence: 81%
“…Ruminants and microorganisms are in constant dynamic balance of mutual dependence and restriction, and forage type can change microbes dramatically to adapt it [25]. The gut-liver axis plays crucial roles in nutrition absorption as the liver receives approximately two-thirds of blood from intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal structure changes continually; at the grazing stage, after 90 days of age, there is an increase in the relative abundance of Thelebolus, a genus that contributes to host immunity and by 180 days of age, there is an increase in the relative abundance of Penicillium, a genus with a strong cellulose degrading capacity [15]. In addition, yaks have adapted to the plateau environment by preferentially harboring protozoa such as rumen ciliates that have evolved to digest mainly fibers [16]. Yaks also alter rumen protozoa at 90 days of age as the dietary fiber content increases, with an increase in the abundance of Dasytricha spp, and a decrease in Entodinium [17], while Isotricha spp.…”
Section: Synergistic Evolution Between Yaks and Microorganismsmentioning
confidence: 99%